Role of Colonoscopy in Management of Lower Gastrointestinal Disorders: Diagnostic & Therapeutic - Birajdar, Dr. Pushkraj Baswant; Thakur, Dr. Sanjeev S.; Bafana, Dr. Pradeep N. (International Journal of Innovative Research in Medical Science, 2017)
A flexible colonoscope has opened the door to the better understanding of the lower gastrointestinal tract. Even to this date people keep on analyzing the usefulness, application, advantages, disadvantages, complications, newer technologies and therapeutic applications of the colonoscope. The endoscopist and industry are working hand in hand to give us fascinating gadgets to learn, investigate and apply to the benefit of our patients. As endoscopy itself is being transformed from the first fiberscope to the modem CCD Video-colonoscope of the 1990s, so has its influence on how gastroenterology is practiced, taught and perceived. The application of lower Gastrointestinal endoscope i.e. colonoscope has been spanned from adults to paediatric age group. The indications are being enlarged, complications are being reduced and the concepts of management are being changed. In open access colonoscopy, the implications of rapid and easy access to endoscopic evaluation is being studied for diagnosis of common but disturbing disorders like per rectal bleeding , chronic pain lower abdomen. The early diagnosis of colonic malignancy to improve the survival rates is well established with the help of colonoscopy.